A non-viscous-featured fractograph in metallic glasses. Issue 6 (21st February 2016) - Yang, G. N.; Shao, Y.; Yao, K. F.
Abstract: A fractograph of non-viscous feature but pure shear-offsets was found in three-point bending samples of a ductile Pd–Cu–Si metallic glass. A sustainable shear band multiplication with large plasticity during notch propagation was observed. Such non-viscous-featured fractograph was formed by a crack propagation manner of continual multiple shear bands formation in front of the crack-tip, instead of the conventional rapid fracture along shear bands. With a 2D model of crack propagation by multiple shear bands, we showed that such fracture process was achieved by a faster stress relaxation than shear-softening effect in the sample. This study confirmed that the viscous fracture along shear bands could be not a necessary process in ductile metallic glasses fracture, and could provide new ways to understand the plasticity in the shear-softened metallic glasses.